Activation of GSK‐3 disrupts cholinergic homoeostasis in nucleus basalis of Meynert and frontal cortex of rats. Issue 12 (28th June 2017) - Wang, Yue; Tian, Qing; Liu, En‐Jie; Zhao, Li; Song, Jie; Liu, Xin‐An; Ren, Qing‐Guo; Jiang, Xia; Zeng, Juan; Yang, Yu‐Tao; Wang, Jian‐Zhi
Abstract: The cholinergic impairment is an early marker in Alzheimer's disease (AD), while the mechanisms are not fully understood. We investigated here the effects of glycogen synthase kinse‐3 (GSK‐3) activation on the cholinergic homoeostasis in nucleus basalis of Meynert (NBM) and frontal cortex, the cholinergic enriched regions. We activated GSK‐3 by lateral ventricular infusion of wortmannin (WT) and GF‐109203X (GFX), the inhibitors of phosphoinositol‐3 kinase (PI3‐K) and protein kinase C (PKC), respectively, and significantly decreased the acetylcholine (ACh) level via inhibiting choline acetyl transferase (ChAT) rather than regulating acetylcholinesterase (AChE). Neuronal axonal transport was disrupted and ChAT accumulation occurred in NBM and frontal cortex accompanied with hyperphosphorylation of tau and neurofilaments. Moreover, ChAT expression decreased in NBM attributing to cleavage of nuclear factor‐κB/p100 into p52 for translocation into nucleus to lower ChAT mRNA level. The cholinergic dysfunction could be mimicked by overexpression of GSK‐3 and rescued by simultaneous administration of LiCl or SB216763, inhibitors of GSK‐3. Our data reveal the molecular mechanism that may underlie the cholinergic impairments in AD patients.